Development of Gait Recognition in NI LabVIEW - Salánki, Dániel; Sarvajcz, Kornél (International Journal of Engineering and Management Sciences, 2018)
Nowadays, one of the most significantly improving area in security is the world of biometric identifiers. Within the biometric identifiers, the research group is working with the gait recognition speciality. The research group realized a complex gait recognition system in NI LabVIEW, that can detect more reference points simultaneously with a universal camera and is capable of suiting predetermined curves on the detected points. Moreover, the program can compare the functions suited on the reference curve and the actual curve and evaluate if the two gait images are the same or not. In the program there is a saving and a reloading function which contributes to the production of the reference gait image. The foot analysis program before the gait recognition is designed to improve accuracy. The self-developed gait recognition system was tested on more persons and the False Acceptance Rate (FAR) was zero.